Acupuncture for Chronic Pain in the Vermont Medicaid Population: A Prospective, Pragmatic Intervention Trial - Robert T Davis MS, LAc; Gary Badger MS; Kristina Valentine MS; Alexander Cavert MS; Remy R Coeytaux MD, PhD (SAGE Publishing, 2018)
Introduction In response to the opioid crisis, the 2016 Vermont legislature commissioned a study to assess acupuncture for patients with chronic pain in the Vermont Medicaid population. Objective To assess the feasibility, acceptability, and effectiveness of acupuncture provided by licensed acupuncturists for Vermont Medicaid patients with chronic pain. Methods A total of 156 Medicaid patients with chronic pain were offered up to 12 acupuncture treatments within a 60-day period at the offices of 28 Vermont licensed acupuncturists. PROMIS® questionnaires were administered prior to and at the end of the treatment period to assess changes in pain intensity, pain interference, physical function, fatigue, anxiety, depression, sleep disturbance, and social isolation. Questionnaires also captured patients' overall impressions of treatments as well as self-reported changes in medication use and work function. Results One hundred eleven women (71%) and 45 men (29%) with a wide range of pain complaints received a mean of 8.2 treatments during the intervention period. Measurements captured prior to and at the end of the treatment period showed significant improvements in group mean pain intensity, pain interference, physical function, fatigue, anxiety, depression, sleep disturbance, and social isolation as assessed by Patient-Reported Outcomes Measurement Information System (PROMIS) measures (paired t tests, P  < .01). Fifty-seven percent of patients using analgesic (nonopioid) medication reported reductions in use. Thirty-two percent of patients using opioid medication reported reductions in use of opioid medication following the intervention. Seventy-four percent of employed patients reported improved capacity to work. Ninety-six percent of patients said that they would recommend acupuncture to others with chronic pain, and 91% reported qualitative improvements, including physical (31%), functional/behavioral (29%), and psycho-emotional (24%) improvements. Conclusions Our findings demonstrate that acupuncture treatment for chronic pain is feasible and well received by patients in the Vermont Medicaid population. Receiving care from Licensed Acupuncturists was associated with significant improvements in physical, functional, psycho-emotional, and occupational outcomes compared with before receiving acupuncture treatments.